PERAN PENGADILAN HUBUNGAN INDUSTRIAL PADA PENGADILAN NEGERI PADANG KELAS IA DALAM MEMBERIKAN KEPASTIAN HUKUM TERHADAP PERKARA PEMUTUSAN HUBUNGAN KERJA - Sinaga, Rustan (Kopertis Wilayah X, 2018)
After the enactment of Law No. 2 of 2004 on Industrial Relations Dispute Settlement, the implication of handling disputes disputes becomes the authority of the Industrial Relations Court at the local District Court. In addition to the court (litigation) settlement disputes termination disputes may also be settled out of court (non litigation). The Industrial Relations Court at the IA District Court handled several termination matters. In this study the authors will focus on the settlement through the judiciary (litigation). The problems discussed in this paper is the Role of Industrial Relations Court in Providing Legal Certainty to Termination of Employment Case (PHK) and Implementation of Decision. This study is juridical normative. Based on this research the authors draw the conclusion that the Industrial Relations Court has not played a role in Giving Legal Certainty to Termination Employment Case. The Industrial Relations Court only performs its role in accordance with applicable law. Implementation of the PHI's decision that the losing party tended to file a cassation appeal. Parties that have not / do not want to implement the contents of the decision of the IRC are caused by the absence of sanctions in Law Number 13 Year 2003 concerning Manpower and Law Number 2 Year 2004 on Industrial Relations Dispute Settlement.